Impact of size of the tumour, persistence of estrogen receptors, progesterone receptors, HER-2 neu receptors and Ki67 values on positivity of sentinel lymph node, in patients with early breast cancer - Борислав Кондов (My University, 2018)
In surgical treatment of breast carcinoma axillary lymphadenectomy has diagnostic role (clinical staging), and therapeutic role (removing cancerous lymph nodes, which is less important due to the systemic treatment with medications). The introduction of “sentinel lymph node biopsy”, is possible due to analyze of one or few lymph nodes, to determines the lymph node status of all others lymph nodes and enables a minimally invasive treatment approach. Determining the criteria (primary tumor size, presence of estrogen and progesterone receptors, Ki67 index value and HER-2 status) that impacts positivity in the “sentinel lymph node” or in other nodes in the axilla will enable the application of the “sentinel lymph node biopsy” technique only in cases when it is really necessary, without exposing the patient to residual disease in the axillary lymph nodes. Aims: 1. Introducing the method for “sentinel lymph node detection and biopsy” in daily clinical practice. 2. Examining the impact of tumor size, presence of estrogen receptors, progesterone receptors in tumor cells, Ki67 index value and HER-2 positive status, positivity of the “sentinel lymph node” in the axilla in patients with early breast cancer. 3. Examining the impact of tumor size, presence of estrogen receptors, progesterone receptors in tumor cells, Ki67 index value and HER-2 positive status, positivity of the “non-sentinel lymph node” in the axilla in patients with early breast cancer with positive “sentinel lymph node”. Materials and methods: A prospective study was conducted on 80 patients with early breast cancer (T1,2 N0 M0) in which the “sentinel lymph node” were detected with preoperative application of radio-collide and Methylene blue dye 0.005%. After the biopsy of these lymph nodes the breast were radically operated, followed by histopathological analysis of the “sentinel lymph node” and primary breast cancer histopathology. In patients with metastatic disease in the “sentinel lymph node” ( on frozen section or paraffin section), a complete lymphadenectomy were performed on the other lymph nodes in the axilla. Breast carcinoma of all patients undergone a routine examination with immunohistochemical analysis for the presence of estrogen receptors, progesterone receptors, Ki67 and HER-2. A total of 81 patients with same disease characteristics were examined in the control group, and patients undergone radical surgery of the breast with complete axillary lymphadenectomy. All data was added to the Excel database, and the statistical analysis was completed in statistical software Statistics 10. Results: After having analyzed the results we can conclude that we tested two homogenous and comparable groups. There is no statistically significant difference between the basic parameters of these groups, therefore the groups are comparable. Naturally, some of the parameters are different (complete lymphadenectomy was performed in the control group) therefore there is a different number of lymph nodes removed. During the research we found the statistically significant predictive role of Ki67 2 + (p=0.012), progesterone receptors (+) of tumor cells (p=0.045) on the positivity of the “sentinel lymph node”. During the research we found the statistically significant predictive role of tumor size (p=0.024) and Кi67 3+ (p=0.013), impacts the positivity of the “non sentinel lymph node”. With multiple regression analysis we found that tumor size is statistically significant criteria for the positivity of lymph nodes in the axilla in control group patients (p=0.014). There were no intraoperative complications in any of the two groups. Early complications were significantly more frequent in the control group and we found significantly different results regarding the presence of seroma (Hi2=68,3 p=0,001), pain in the axilla (Hi2=28,8 p=0,001), sensory deficit (Hi2=102,1 p=0,001), shoulder pain, swelling of the hands and the arms. Some of these are prolonged complications therefore there are significant differences between the control group and the test group regarding pain in the axilla (Hi2=8,3 p=0,001), sensory deficit (Hi2=69,6 p=0,001) and shoulder pain (Hi2=45,8 p=0,001). In reality, there is even a greater difference knowing that patients in the test group underwent “sentinel lymph node detection and biopsy” and if metastatic deposit is found in the lymph node (which is the case with 30% of the patients) a complete axillary lymphadenectomy is performed. This is the most significant outcome of this study.
Влијанието на големината на тумор, присуство на естрогени рецептори, прогестеронски рецептори на туморската клетка, вредноста на Ki67 и HER-2 позитивност врз позитивитет на “sentinel” лимфна жлезда („жлезда стражар“) кај пациенти со ран карцином на дојка
Keywords: breast carcinoma; “sentinel lymph node biopsy”; estrogen receptors; progesterone receptors; Ki67; HER-2